Colonization of endophyte Acremonium sp. D212 in Panax notoginseng and rice mediated by auxin and jasmonic acid. Issue 9 (26th February 2020) - Han, Li; Zhou, Xuan; Zhao, Yiting; Zhu, Shusheng; Wu, Lixia; He, Yunlu; Ping, Xiangrui; Lu, Xinqi; Huang, Wuying; Qian, Jie; Zhang, Lina; Jiang, Xi; et al.
Abstract: Endophytic fungi can be beneficial to plant growth. However, the molecular mechanisms underlying colonization of Acremonium spp. remain unclear. In this study, a novel endophytic Acremonium strain was isolated from the buds of Panax notoginseng and named Acremonium sp. D212. The Acremonium sp. D212 could colonize the roots of P. notoginseng, enhance the resistance of P. notoginseng to root rot disease, and promote root growth and saponin biosynthesis in P. notoginseng. Acremonium sp. D212 could secrete indole‐3‐acetic acid (IAA) and jasmonic acid (JA), and inoculation with the fungus increased the endogenous levels of IAA and JA in P. notoginseng . Colonization of the Acremonium sp. D212 in the roots of the rice line Nipponbare was dependent on the concentration of methyl jasmonate (MeJA) (2–15 μmol/L) and 1‐naphthalenacetic acid (NAA) (10–20 μmol/L). Moreover, the roots of the JA signaling‐defective coi1‐18 mutant were colonized by Acremonium sp. D212 to a lesser degree than those of the wild‐type Nipponbare and miR393b‐overexpressing lines, and the colonization was rescued by MeJA but not by NAA. It suggests that the cross‐talk between JA signaling and the auxin biosynthetic pathway plays a crucial role in the colonization of Acremonium sp. D212 in host plants. Abstract : In this study, we report a new endophytic fungus, named Acremonium sp. D212, which isolated from traditional Chinese medicine Panax notoginseng . It is the first time revealed that the colonization of the fungus in host plants was mediated by the interaction of hormones auxin and jasmonic acid.